Criminality and apartment prices: A study for Rio de Janeiro, Brazil - Luiz Andrés Paixão (Romanian Journal of Regional Science, 2025)
Violence is one of the biggest problems in Brazilian society, Brazil being one of the most violent countries in the world. Rio de Janeiro is the second largest Brazilian city both in economic and population terms and is the most famous Brazilian city in the world. Measuring the social cost of violence is an important task to understand the Rio de Janeiro reality. There is some consensus in literature that housing prices are very sensitive to environment changes and there is a negative relationship between violence rates and housing price. We developed a hedonic price model to quantitatively determine the effect of violence on apartments price in Rio de Janeiro, using homicide and robbery rates as criminality proxies. A set of control variables were included since these variables were relevant to Rio de Janeiro’s apartment market. We used spatial econometric frameworks to deal with the spatial nature of the data. Our results show that the increase in criminal violence is linked to the decrease in apartments prices in Rio de Janeiro.